Organoleptic Quality of Fresh Vaname Shrimp (Litopenaeus vannamei) Marketed in Modern Markets of Makassar City - Sitti Hardiyanti Rachman; Kasmiati Kasmiati; Fahrul Fahrul (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research seeks to determine the organoleptic quality of fresh vaname shrimp which are marketed in modern market of Makassar City. The research was conducted from December 2019 to February 2020, in three modern markets with each representing the eastern, central, and western parts of Makassar. Samples were taken three times in each market during 10.00-11.00. The organoleptic testing consisted several parameters; appearance, smell, and meat/texture, and was performed at the Laboratory of Fisheries Product Quality Implementation Agency (BPMPP) of South Sulawesi Province. In addition, shrimp temperature and pH tests were performed shortly after sampling. The data obtained were analyzed descriptively and presented in tabular form. The research results showed that vaname shrimp marketed in three modern markets of Makassar City were categorized as fresh shrimp which were within the safe limit for consumption. Compared to the Indonesian National Standard (01-2728.1-2018) regarding the organoleptic safety of fresh shrimp, this results showed values meeting safety standards. Keywords: Organoleptic quality, vaname shrimp, modern market